Sarcopenia and catastrophic health expenditure by socio‐economic groups in China: an analysis of household‐based panel data. Issue 3 (26th April 2022) - Ye, Chen; Zheng, Xu; Aihemaitijiang, Sumiya; Wang, Ruoyu; Halimulati, Mairepaiti; Huang, Xiaojie; Zhang, Zhaofeng
Abstract: Background: Sarcopenia was thought to be associated with adverse outcomes and will cause lots of health expenditure. But the relationship between sarcopenia and catastrophic health expenditure (CHE) had been little explored. Here, we examined the distribution of sarcopenia in relation to medical and payment burdens. Methods: We used data from three waves of China Health and Retirement Longitudinal Study including 14 130 participants from 9077 households aged over 50 years old. Sarcopenia was operationalized according to the Asian Working Group for Sarcopenia 2019. Medical expenditure was obtained by self‐reported data, and CHE was identified by WHO definitions. We used the negative binomial regression model and logistic mixed‐effects models to examine the associations between sarcopenia and medical and CHE. Results: A total of 14 130 participants [52.2% female, aged 60.8 (SD 9.3)] from 9077 households were included in this study. The prevalence of sarcopenia was 19.8%, 11.9% for moderate sarcopenia, and 7.9% for severe sarcopenia, respectively. We identified 1416 household CHE events in all three waves. Severe sarcopenia was associated with an increase in the number of inpatient visits [incidence rate ratio 1.31, 95% confidence interval (CI): 1.03–1.66, P  = 0.03] and the risk of CHE (odds ratio: 1.04, 95% CI: 1.01–1.07, P  < 0.01). We saw similar effects in health service use of sarcopenia in different socio‐economic groups. Moderate sarcopenia increased the risk of CHE in the lowest socio‐economic group (odds ratio 1.03, 95% CI: 1.01–1.06, P  = 0.03) and had no statistical significance in other groups. The association between severe sarcopenia and CHE did not attenuate after the adjustment of disease factors. Conclusions: Severe sarcopenia may increase the risk of CHE. Timely and effective intervention on moderate sarcopenia from severe sarcopenia will contribute to reduce the health burden.